2022
DOI: 10.3390/jof8060567
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Mycoparasitism of Clonostachys rosea against Botrytis cinerea Using GFP

Abstract: Clonostachys rosea is an important mycoparasite, with great potential for controlling numerous plant fungal diseases. Understanding the mechanisms and modes of action will assist the development and application of this biocontrol fungus. In this study, the highly efficient C. rosea 67-1 strain was marked with the green fluorescent protein (GFP), and the transformant possessed the same biological characteristics as the wild-type strain. Fungal interactions with Botrytis cinerea during co-culture and encounter o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…By contrast, antifungal activities were greatly reduced for CrGlu6-deficient mutants, and control efficacy against soybean rot was significantly decreased in the greenhouse. Research on the direct interaction of the mycoparasite and its prey, including recognition, enwind, penetration, and disintegration will be very interesting [69]. Research on these phenotypes is underway to explore the mechanisms connecting the CrGlu6 gene to the vegetative growth and biocontrol activities of C. chloroleuca.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, antifungal activities were greatly reduced for CrGlu6-deficient mutants, and control efficacy against soybean rot was significantly decreased in the greenhouse. Research on the direct interaction of the mycoparasite and its prey, including recognition, enwind, penetration, and disintegration will be very interesting [69]. Research on these phenotypes is underway to explore the mechanisms connecting the CrGlu6 gene to the vegetative growth and biocontrol activities of C. chloroleuca.…”
Section: Discussionmentioning
confidence: 99%
“…Clonostachys rosea is a hyperparasitic fungus capable of invading various plant-pathogenic fungi, including Botrytis cinerea, Fusarium spp., Rhizoctonia solani, and Sclerotinia sclerotiorum (Barnett and Lilly, 1962;Cota et al ., 2008;Jensen et al ., 2000;Luongo et al ., 2005;Rodríguez et al ., 2011), with C. rosea strain 67-1 being highly efficient for biocontrol (Zhang et al ., 2007;Ma et al ., 2011;Sun et al ., 2018). Hasan et al (2022) showed that the GFP-marked C. rosea strain 67-1 exerts antagonistic activities against B. cinerea both in vitro and on tomato leaves. The hyperparasite is able to penetrate its host, absorb its nutrients, and eventually disintegrate all of its cells.…”
Section: Hyperparasitic Fungi and Biological Controlmentioning
confidence: 98%
“…Furthermore, Zhang et al (2020) [38] first reported on the possibility of root rot in saffron plants specifically caused by P. solitum. C. rosea was previously used as a biocontrol agent because of its active mycoparasitism [39,40]. However, in recent years, researchers identified root rot in grain legumes and medicinal crops caused by C. rosea [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%